2012
DOI: 10.3233/jad-2012-121156
|View full text |Cite
|
Sign up to set email alerts
|

MRI Signatures of Brain Macrostructural Atrophy and Microstructural Degradation in Frontotemporal Lobar Degeneration Subtypes

Abstract: Brain magnetic resonance imaging (MRI) studies have demonstrated regional patterns of brain macrostructural atrophy and white matter microstructural alterations separately in the three major subtypes of frontotemporal lobar degeneration (FTLD), which includes behavioral variant frontotemporal dementia (bvFTD), semantic dementia (SD), and progressive nonfluent aphasia (PNFA). This study was to investigate to what extent the pattern of white matter microstructural alterations in FTLD subtypes mirrors the pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 51 publications
9
58
0
3
Order By: Relevance
“…This pattern was consistent with the results of previous VBM studies performed in FTLDcontrol series where the underlying genetic causes were not known [15]. The temporal atrophic clusters were located in the left middle temporal gyrus, temporal pole and superior temporal gyrus and in frontal regions.…”
Section: Comparison Between Sporadic Ftd Versus Hc/sqstm1 Noncarrierssupporting
confidence: 81%
See 2 more Smart Citations
“…This pattern was consistent with the results of previous VBM studies performed in FTLDcontrol series where the underlying genetic causes were not known [15]. The temporal atrophic clusters were located in the left middle temporal gyrus, temporal pole and superior temporal gyrus and in frontal regions.…”
Section: Comparison Between Sporadic Ftd Versus Hc/sqstm1 Noncarrierssupporting
confidence: 81%
“…Although, we have previously identified patterns of regional brain atrophy associated with other genetic variants with similar study designs to the present one [15,17,18], our study still has several limitations: the number of subjects is low, but this was expected considering the low frequency of SQSTM1 mutations among FTD patients. In addition, the distribution of the three populations studied (FTD/SQSTM1 carriers, Sporadic FTD and HC/SQSTM1 noncarriers) was not homogeneous among centers.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…For example, a previous study applied VBM and diffusion tensor imaging (DTI) to separate FTLD subtypes (i.e., bvFTD, SD, and PNFA) from healthy controls. The authors revealed that DTI measurement, particularly radial diffusivity, provided better accuracies (67.6%-81.4%) than gray matter atrophy (45.7%-65.7%) or white matter atrophy (47.4%-59.2%) (41). Moreover, Dukart et al demonstrated classification accuracy of 60.0% using structural MRI, 80.0% using 18 F-FDG PET, and 94.3% using combined 18 F-FDG PET and structural MRI to separate AD from FTLD patients (18).…”
Section: Classification Accuraciesmentioning
confidence: 99%
“…Nine whole-brain studies of FTD were included (Zhang, Schuff et al 2009, Hornberger, Geng et al 2011, Zhang, Tartaglia et al 2013, Tovar-Moll, de Oliveira-Souza et al 2014, Downey, Mahoney et al 2015. When FTD patients were compared to ALS and ALS-FTD patients, TBSS revealed significant changes involving the callosal tracts; the forceps minor, and ILF than in CST .…”
Section: Whole Brain Analysismentioning
confidence: 99%